Cross-pollination of fruits - Webb, Frank Cooper (My University, 1904)
Introduction: The phenomenon of barrenness in orchards composed of a single variety has frequently been noticed. At the same time it has been observed that the same variety when grown in mixed orchards has fruited well. This has led to more careful observations and experiments involving tests of many varieties of the cultivated fruits for self-sterility with the result that self-sterility has been found much more common than was at first supposed. By self-sterility is meant the inability to set fruit when the stigma can only receive the pollen from the same variety. The pollen from a different tree of the same variety is no more potent than that of the same tree. This is not surprising when we think that by the method of propagation of varieties each tree is really a part of the original tree.
Citation: Webb, Frank Cooper. Cross-pollination of fruits. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Cross-pollination; fruit pollination; types of pollination; Theses; Manuscripts (documents)